Cationic and Biocompatible Polymer/Lipid Nanoparticles as Immunoadjuvants - Yunys Pérez-Betancourt; Péricles Marques Araujo; Bianca de Carvalho Lins Fernandes Távora; Daniele Rodrigues Pereira; Eliana Lima Faquim-Mauro; Ana Maria Carmona-Ribeiro (MDPI AG, 2021)
Nanostructures have been of paramount importance for developing immunoadjuvants. They must be cationic and non-cytotoxic, easily assembling with usually oppositely charged antigens such as proteins, haptens or nucleic acids for use in vaccines. We obtained optimal hybrid nanoparticles (NPs) from the biocompatible polymer poly(methyl methacrylate) (PMMA) and the cationic lipid dioctadecyl dimethyl ammonium bromide (DODAB) by emulsion polymerization of methyl methacrylate (MMA) in the presence of DODAB. NPs adsorbed ovalbumin (OVA) as a model antigen and we determined their adjuvant properties. Interestingly, they elicited high double immune responses of the cellular and humoral types overcoming the poor biocompatibility of DODAB-based adjuvants of the bilayer type. The results suggested that the novel adjuvant would be possibly of use in a variety of vaccines.